Simple and low‐cost tracking generator design in envelope tracking radio frequency power amplifier system for WCDMA applications. Issue 10 (1st July 2013) - Yusoff, Zubaida; Lees, Jonathan; Chaudhary, Muhammad Akmal; Carrubba, Vincenzo; Choi, Heungjae; Tasker, Paul; Cripps, Steve C.
Abstract : A simple analogue technique called auxiliary envelope tracking, or AET, is presented, which is shown to be capable of improving the efficiency of a radio frequency power amplifier (RFPA). This AET signal is an amplified envelope signal that supplies the drain port of the RFPA. The concept of AET is explained and a theoretical background for the technique is presented. The main feature of this technique lies in the separation of the DC and AC components of the tracking signal. This allows for a very simple and low‐cost tracking generator design that consists of a simple source follower amplifier and an RF broadband transformer. A practical system has been implemented and the measured results are obtained for WCDMA signals. A measurement on the realised system shows a 50% improvement in the drain efficiency at average output power of 33 dBm of a 25 W GaN. This substantial improvement is achieved at a competitive WCDMA signal with peak‐to‐average envelope power ratio of 9.17 dB.